Single stage boost inverter for standalone fuel cell applications - Moraka, Otshepeng Johny (Department of Electrical Engineering, 2017)
The proton exchange membrane fuel cell (PEMFC) is a promising technology that can be manufactured in South Africa because of the platinum catalyst required. South Africa is rich in platinum and, therefore, the PEMFC system can be cost-effectively produced. In residential stationary applications of the PEMFC a power conditioning system is required to convert the de voltage output of the PEMFC to ac voltage. Therefore, the focus of this thesis is to analyse, simulate and design a power electronic dc-ac converter. The power electronic dc-ac converter is based on a transformerless single stage power conversion scheme, which has better weight, volume and efficiency than the commonly used two stage power conversion schemes. The selected topology is the boost inverter that consists of two identical boost converters for boosting and inversion of the PEMFC de voltage. Moreover, it achieves reliable operation under nonlinear loads, sudden load changes and inrush current, using a double loop control strategy. Initially, the double loop control strategy was introduced with proportional integral (Pl) controllers. Recently, with the widespread use of proportional resonant PR controllers, the PI controllers were replaced with PR controllers to achieve zero steady state error for the ac components of the reference. However, during the implementation of the PR controllers on the boost inverter, a significant de offset in the output voltage of the boost inverter was observed, which was due to the mismatch of the boost converters' parameters. The de voltage affects pulsating torque AC machines, accuracy in domestic watt-meter and safety of residual current protection. Furthermore, the output voltages of the boost converters showed a clipping effect, which was caused by the dead time of the switching devices used in the boost converters. An integral term was added to the PR controller to form the controller here called the proportional integral resonant (PIR) controller. This controller achieved satisfactory results of de and ac voltage reference following capability and maintains the same advantages of the PI controllers. However, the efficiency was not high due to the high resistance of the inductor used in the boost inverter system.